Electrochemical device and electronic device using the same
Patent Information
- Application Number
- KR1020237031568
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-18
- Publication Date
- 2026-09-16
- Estimated Expiration
- 2041-03-18
Smart Images

Figure 112023102172530-PCT00003_ABST
Abstract
Description
Technology Field
[0001] This application relates to the field of battery technology, and in particular to electrochemical devices and electronic devices using the same. Background Technology
[0002] As consumer demand for high-energy-density batteries increases, it is generally necessary to form an active material layer with a larger coating weight on the electrode to increase battery capacity. However, since a larger coating weight (thick electrode) typically results in a thicker active material layer, a noticeable thickness difference is created between the insulating layer and the active layer applied to the edges of the electrode to prevent burrs, thereby affecting the appearance of the electrode. Furthermore, when applying the insulating coating layer, the edges of the insulating coating layer form a thick border due to the dual effects of fluid expansion caused by additional stress on the surface of the coating device and flexibility caused by surface tension of the slurry during the drying process. Due to this thick border, the edges bulge when the electrode is wound, and in severe cases, the electrode may break. At the same time, when the electrode is rolled, the tension distribution is uneven and alignment fails to meet requirements, affecting the processing size of the electrode.
[0003] To solve the aforementioned problems, conventional technology generally involves coating an insulating layer larger than the actual required size of the electrode during fabrication and then trimming off the thick border region at the edge of the electrode. However, since the coating size of the insulating layer is larger than the actual required size of the electrode and there is a thick border, it results in excessive material waste. Those skilled in the art need to consider a method that not only improves the appearance of the thick electrode but also eliminates the bulging phenomenon of the insulating layer border, meets the demand for high energy density, and increases the yield of battery products.
[0004] In order to solve the problem caused by the excessive thickness of the coating on the electrode in the prior art, the present embodiment provides an electrochemical device as follows. The electrochemical device comprises an electrode, wherein the electrode comprises a first current collector, a first tab protruding from the first current collector, a first active material layer installed on at least one surface of the first current collector, and an insulating layer installed along a side of the first current collector close to the first tab and adjacent to the first active material layer, wherein the insulating layer comprises a first region and a second region, wherein the first region is installed on one side close to the first tab, and the second region is installed far from the first tab and adjacent to the first active material layer, and the thickness of the insulating layer in the first region is smaller than the thickness of the insulating layer in the second region.
[0005] In a possible embodiment, the first region includes a first surface located far from the first current collector, and the plane on which the first surface is located intersects the plane on which the first current collector is located to form an acute angle α, the thickness of the second region is H, and the width of the insulating layer is W, where W / H ≥ cotα.
[0006] In a possible embodiment, the range of the acute angle α is 5° to 75°.
[0007] In a possible embodiment, the thickness H of the second region ranges from 20 μm to 100 μm, and the width W of the insulating layer ranges from 1 mm to 10 mm.
[0008] In a possible embodiment, the thickness L of the first active material layer ranges from 30 μm to 200 μm.
[0009] In a possible embodiment, the thickness H of the second region and the thickness L of the first active material layer satisfy the relationship 0.3 ≤ H / L ≤ 0.8.
[0010] In a possible embodiment, the coating weight of the first active material layer is 0.06 mg / mm 2 Up to 0.35 mg / mm 2 am.
[0011] In a possible embodiment, the compression density of the first active material layer is 2 g / cc to 6 g / cc.
[0012] In a possible embodiment, the insulating layer comprises inorganic particles and an adhesive, wherein the inorganic particles comprise at least one of boehmite, aluminum oxide, zirconium oxide, boron oxide, or hexagonal boron nitride, and the adhesive comprises at least one of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, or sodium carboxymethylcellulose.
[0013] The present application also provides an electronic device comprising the aforementioned electrochemical device.
[0014] Compared to the prior art, the electrochemical device of the present application installs insulating layers of a first region and a second region with different thicknesses on the outer side of a first active material layer, and makes the thickness of the second region closer to the first active material layer greater than the thickness of the first region farther from the first active material layer, that is, makes the region close to the edge of the insulating layer thinner, and controls so that this thinned region does not extend to the first active material layer, thereby eliminating the thick edge shape and preventing loss of active material in the first active material layer, and overcomes the problem of edge swelling of the electrode by eliminating the thick edge shape under the premise of increasing the energy density of the electrochemical device, and reduces the thickness difference between the first active material layer and the insulating layer. Brief explanation of the drawing
[0015] FIG. 1 is a schematic plan view of an electrochemical apparatus according to one embodiment of the present application. FIG. 2 is a schematic plan view of an electrode of an electrochemical device according to one embodiment of the present application. Figure 3 is a schematic cross-sectional view along the III-III direction of Figure 2. FIG. 4 is a schematic three-dimensional view of an electrochemical apparatus according to one embodiment of the present application. Specific details for implementing the invention
[0016] Hereinafter, specific details for carrying out the invention will be described in detail with reference to the attached drawings of the present application.
[0017] The following description will refer to the accompanying drawings to more completely explain the contents of this application. The accompanying drawings illustrate exemplary embodiments of this application. However, this application may be embodied in various other forms and is not limited to the embodiments described herein. These exemplary embodiments are provided to make this application thorough and complete and to fully convey the scope of this application to those skilled in the art. Identical reference numerals indicate identical elements.
[0018] The terms used herein are for the purpose of describing specific embodiments only and are not intended to limit the invention. As used herein, the singular form includes the plural form unless the context clearly indicates otherwise. Furthermore, it will be understood that when used herein, the words “comprising” and / or “comprising” or “having” and / or “having” specify the presence of the mentioned feature, region, integer, step, action, element, and / or component, but do not exclude the addition of one or more other features, regions, integers, steps, actions, elements, components, and / or groups thereof.
[0019] Unless otherwise defined, all terms used herein, including technical and scientific terms, have the same meaning as generally understood by those skilled in the art to which the present invention pertains. Furthermore, it will be understood that terms such as those defined in commonly used dictionaries should be interpreted as having a meaning consistent with their meaning in the context of the relevant technology and the present invention, and should not be interpreted in an ideal or overly formal sense unless explicitly defined so in this specification.
[0020] Exemplary embodiments are described below with reference to the attached drawings. Components depicted in the reference drawings are not necessarily shown in scale, and identical or similar components are assigned identical or similar reference numbers or similar technical terms.
[0021] Hereinafter, specific embodiments of the present application will be described in detail with reference to the attached drawings.
[0022] Referring to FIG. 1, an embodiment of the present application provides an electrochemical device (1) comprising a electrode (10). In one embodiment, the electrochemical device (1) of the present application is described with the lithium-ion battery as an example, but the electrochemical device (1) of the present application is not limited to a lithium-ion battery.
[0023] FIG. 2 is a schematic partial enlarged view of an electrode (10) of an electrochemical device (1) of one embodiment of the present application, wherein the electrode (10) comprises a first current collector (11), a first tab (12), a first active material layer (13), and an insulating layer (14) as shown. Here, the first tab (12) protrudes from the first current collector (11), the first active material layer (13) is installed on at least one surface of the first current collector (11), and the insulating layer (14) is installed along the side of the first current collector (11) close to the first tab (12) and is adjacent to the first active material layer (13). The insulating layer (14) includes a first region (141) and a second region (142), the first region (141) is installed on one side close to the first tap (12), and the second region (142) is installed between the first region (141) and the first active material layer (13) and is adjacent to the first region (141) and the first active material layer (13). Along a direction perpendicular to the surface of the first current collector (11) on which the insulating layer (14) is installed, the thickness of the insulating layer (14) located in the first region (141) is smaller than the thickness of the insulating layer (14) located in the second region (142). In one embodiment, the thickness of the insulating layer (14) located in the first region (141) is smaller than the thickness of the insulating layer (14) located in the second region (142), which means that the thickness of each insulating layer (14) located in the first region (141) is smaller than the thickness of the insulating layer (14) located in the second region (142). In another embodiment, the thickness of the insulating layer (14) located in the first region (141) is smaller than the thickness of the insulating layer (14) located in the second region (142), which means that the maximum thickness of the insulating layer (14) located in the first region (141) is smaller than the minimum thickness of the insulating layer (14) located in the second region (142).
[0024] An insulating layer having a first region (141) and a second region (142) with different thicknesses is installed on the outer side of the first active material layer (13), and the thickness of the second region (142) near the first active material layer (13) is made greater than the thickness of the first region (141) far from the first active material layer (13), that is, the region near the edge of the electrode (10) of the insulating layer (14) is made thin, and this thinned region is controlled so that it does not extend to the first active material layer (13), thereby removing the thick edge shape and preventing loss of active material of the first active material layer (13), and under the premise of increasing the energy density of the electrochemical device (1), the problem of the edge swelling of the electrode (10) is overcome by removing the thick edge shape and reducing the thickness difference between the first active material layer (13) and the insulating layer (14).
[0025] There are no specific limitations on the anode of the embodiments of the present application as long as the purpose of the present application can be achieved. For example, the anode generally comprises an anode current collector and an anode active material layer. There are no specific limitations on the anode current collector and it generally comprises at least one of aluminum foil, aluminum alloy foil, or a composite current collector. The anode active material layer comprises an anode active material, and there are no specific limitations on the anode active material; it may comprise at least one of lithium nickel-cobalt-manganese oxide, lithium nickel-cobalt-aluminum oxide, lithium iron phosphate, a lithium manganese-rich material, lithium cobaltate, lithium manganese oxide, lithium iron manganese phosphate, or lithium titanium oxide.
[0026] The cathode of the embodiments of the present application is not subject to any particular limitations as long as it can achieve the purpose of the present application. For example, the cathode generally comprises a cathode current collector and a cathode active material layer. Here, the cathode current collector is not subject to any particular limitations and may include at least one of copper foil, aluminum foil, aluminum alloy foil, and a composite current collector. The cathode active material layer comprises a cathode active material, and there are no particular limitations on the cathode active material; it may include at least one of artificial graphite, natural graphite, mesophase carbon microspheres, soft carbon, hard carbon, silicon, silicon carbon, lithium titanate, etc.
[0027] Here, the electrode plate (10) may be an anode or a cathode, and in the embodiments of the present application, the present application is described by giving an example where the electrode plate (10) is an anode. Correspondingly, the first active material layer (13) may be an anode active material layer or a cathode active material layer, and in the embodiments of the present application, the present application is described by giving an example of an anode active material layer. In one embodiment, the first tab (12) protrudes from the first current collector (11), that is, the first tab (12) protrudes in a direction away from the center region of the first current collector (11) than the edge of the first current collector (11). In this embodiment, the fact that the first tab (12) protrudes from the first current collector (11) means that the first tab (12) is formed integrally with the first current collector (11) and the edge of the first current collector (11) is extended and formed convexly. In other embodiments, the first tab (12) and the first current collector (11) may have a non-integrated structure, and the first tab (12) may be connected to the first current collector (11), for example by welding, before coating the insulating layer (14) on the electrode (10).
[0028] In one embodiment, the first active material layer (13) is installed on at least one surface of the first current collector (11), for example, the first active material layer (13) may be installed on both sides of the first current collector (11).
[0029] In one embodiment, the insulating layer (14) is coated on the surface of the first current collector (11) and is adjacent to the first active material layer (13). The insulating layer (14) is installed at the edge of the first current collector (11) and can cover at least the edge of the first current collector (11) after it has been cut, and covers the cut burr located at this edge to prevent the burr from penetrating the separator. Additionally, the insulating layer (14) covers at least a portion of the junction between the first current collector (11) and the first tab (12), and covers the cut burr at one end of the first tab (12) adjacent to the first current collector (11) to prevent the burr from penetrating the separator.
[0030] As illustrated in FIG. 3, the first region (141) includes a first surface (143), and the plane on which the first surface (143) is located intersects the plane on which the first current collector (11) is located to form an acute angle α, the thickness of the second region (12) is H, and the width of the insulating layer is W, where W / H ≥ cotα.
[0031] In one embodiment, the cross-section along the polarity thickness direction of the insulating layer (14) is trapezoidal, specifically, the thickness of one side (i.e., the second region (142)) adjacent to the first active material layer (13) of the insulating layer (14) is nearly the same, and the side far from the first active material layer (13) of the insulating layer (14) and close to the first tab (12) is the first region (141), and the thickness of the insulating layer (14) gradually decreases toward the first tab (12) side at the junction between the first region (141) and the second region (142) so that the first surface (143) and the first current collector (11) intersect to form the acute angle α described above.
[0032] In one embodiment, W / H <cotα인 경우, 제1 집전체(11)를 절단하여 제1 탭(12)을 얻는 과정에서, 절연층(14)의 극편 두께 방향을 따르는 단면은 대략 사다리꼴이 아니라 대략 삼각형일 것이다. 즉, 절연층(14)에 가까운 제1 활성물질층(13)의 부분이 제거되어, 전기화학장치(1)의 전체 에너지 밀도가 감소하고 에너지 손실이 발생할 수 있으며, 제1 활성물질층(13)과 절연층(14)의 경계가 흐려질 수 있다.
[0033] In one embodiment, the range of the acute angle α is 5° to 75°. If the acute angle α is less than 5°, the insulating layer (14) may not meet the angle requirements during the thinning process, and if the acute angle α is greater than 75°, the average thickness of the insulating layer (14) in the first region (141) is too large, and the edge of the electrode (10) may bulge. In one embodiment, the acute angle α can be obtained by acquiring an image of the cross-section of the insulating layer (14) using a CCD camera and measuring the angle of the region corresponding to the acute angle α on the image.
[0034] In one embodiment, the thickness of the insulating layer (14), i.e., the thickness of the second region, can be measured using a micrometer or a CCD camera. For example, a electrode (10) of a predetermined length including cross-sections of the first region (141) and the second region (142) on at least one side is cut or selected, and the thickness of the insulating layer (14) is obtained by measuring the second region (142) on the electrode (10) multiple times with a micrometer. For example, after measuring the thickness of the second region (142) 15 times each, the average value of the multiple measurements is taken as the thickness of the second region (142). Alternatively, a surface including cross-sections of the first region (141) and the second region (142) is captured using a CCD camera, and the thickness of the insulating layer (14) is obtained through a measuring tool (e.g., software) that matches the CCD camera, and another image or another part of the same image is repeatedly acquired multiple times (e.g., 15 times) to obtain the average of the thicknesses measured multiple times to obtain the thickness of the insulating layer (14).
[0035] In one embodiment, the width of the insulating layer (14) can be measured by a CCD camera. For example, an image of the insulating layer (14) including a continuous first region (141) and a second region (142) can be captured using a CCD camera, specifically, an image can be obtained using a CCD camera in a low-magnification state, and the width of the insulating layer (14) is obtained by setting both edges of the insulating layer (14) through a measuring tool (e.g., software) that matches the CCD camera, and the width of the insulating layer (14) is obtained by repeatedly acquiring different images or different parts of the same image multiple times (e.g., 15 times) and obtaining the average of the widths measured multiple times.
[0036] In one embodiment, the thickness H of the second region (142) ranges from 20 μm to 100 μm, and the width W of the insulating layer (14) ranges from 1 mm to 10 mm. If the thickness H of the second region (142) is less than 20 μm, the thickness of the insulating layer (14) is smaller than the length of a normal burr, so the burr cannot be effectively coated, and there is a risk that the electrochemical device (1) will be short-circuited, and if the thickness of the second region (142) is greater than 100 μm, the electrode (10) may not meet the cold pressure parameter requirements.
[0037] In one embodiment, the thickness L of the first active material layer (13) ranges from 30 μm to 200 μm. The thickness H of the second region (142) and the thickness L of the first active material layer (13) satisfy the relationship 0.3 ≤ H / L ≤ 0.8. If the ratio is too small and the insulating layer (14) is too thin, burrs cannot be prevented, and if the ratio is too large and the insulating layer is too thick, it is difficult to achieve the set compression density during the cold pressing process of the electrode (10).
[0038] In one embodiment, the coating weight of the first active material layer (13) is 0.06 mg / mm 2 Up to 0.35 mg / mm 2 is. In one embodiment, the weight of the first active material layer (13) or electrode (10) per unit area can be measured with an analytical balance of 1 / 10,000 and the following formula
[0039] Coating weight = (Polyde weight - Current collector weight) / Plate area
[0040] The coating weight is calculated by the above method, and the average value is taken. The coating weight is 0.06 mg / mm 2 If it is less than, the energy density is low, making it difficult to meet the requirements, or problems such as particles or scratches are likely to occur in the first active material layer (13). Coating weight is 0.35 mg / mm 2If it is larger, processing problems such as difficulty drying or cracking of the electrode (10) may occur, and the thickness is too thick, making it difficult to implement the coating process, and the first active material layer (13) (e.g., an active material made of lithium iron phosphate) easily cracks and does not help in the diffusion of lithium ions, which has a negative effect on electrochemical circulation.
[0041] In one embodiment, the compression density of the first active material layer (13) is 2 g / cc to 6 g / cc. In one embodiment, the weight of the first active material layer (13) or electrode (10) per unit area can be measured using an analytical balance of 1 / 10,000, and furthermore, the compression density can be calculated as (weight of the insulating layer electrode per unit area - weight of the current collector) / thickness of the insulating layer excluding the substrate, and the average value can be calculated. If the compression density is too low (less than 2 g / cc), the amount of active material per unit volume is small, resulting in low energy density and making it difficult to meet the requirements; if the compression density is too high (6 g / cc or more), the porosity of the first active material layer (13) is too small, which weakens the ion transfer ability, or the internal resistance (DCR) is too high, or the electrode (10) becomes embrittled, making it easy for the band to break during the cold pressing process.
[0042] In one embodiment, the insulating layer (14) comprises inorganic particles and an adhesive, wherein the inorganic particles comprise at least one of boehmite, aluminum oxide, zirconium oxide, boron oxide, or hexagonal boron nitride, and the adhesive comprises at least one of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, or sodium carboxymethylcellulose.
[0043] The electrochemical device of the present application may further include a separator, which separates the anode and cathode, prevents short circuits within the electrochemical device, and allows the free passage of electrolyte ions to complete the electrochemical charging and discharging process. In the present application, the separator is not particularly limited as long as it can achieve the purpose of the present application. For example, it may include at least one of polyethylene (PE), polypropylene (PP)-based polyolefin (PO) type separator film, polyester film (e.g., polyethylene terephthalate (PET) film), cellulose film, polyimide film (PI), polyamide film (PA), spandex or aramid film, woven film, non-woven fabric, microporous film, composite film, separator paper, laminated film, spinning film, etc.
[0044] Additionally, the separator may include a substrate layer and a surface treatment layer. The substrate layer may be a nonwoven fabric, film, or composite film having a porous structure, and the material of the substrate layer may include at least one of polyethylene, polypropylene, polyethylene terephthalate, and polyimide. In one embodiment, a polypropylene porous film, a polyethylene porous film, a polypropylene nonwoven fabric, a polyethylene nonwoven fabric, or a polypropylene-polyethylene-polypropylene porous composite film may be used. In one embodiment, the surface treatment layer is installed on at least one surface of the substrate layer, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing a polymer and an inorganic material.
[0045] Additionally, for example, the inorganic layer may include inorganic particles and an adhesive, and the inorganic particles are not particularly limited and may be selected from at least one of, for example, aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, and barium sulfate. The adhesive is not particularly limited and comprises one selected from polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyamide, polyacrylonitrile, polyacrylates, polyacrylic acids, polyacrylic acid salt, polyethylene pyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene, and polyhexafluoropropylene, and combinations thereof. For example, the polymer layer comprises a polymer, and the polymer material comprises at least one of polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylic acid salt, polyethylene pyrrolidone, polyvinyl ether, polyvinylidene fluoride, or poly(vinylidene fluoride-hexafluoropropylene).
[0046] The electrochemical apparatus of the present application may also include an electrolyte, and the electrolyte may be one or more of a gel electrolyte, a solid electrolyte and an electrolyte solution, and the electrolyte solution includes a lithium salt and a non-aqueous solvent.
[0047] In one embodiment, when the electrochemical device (10) is a lithium-ion battery, the lithium salt is selected from one or more of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, LiSiF6, LiBOB, and lithium difluoroborate. For example, the lithium salt may be selected as LiPF6, because LiPF6 can provide relatively high ionic electrical conductivity and improve cycle characteristics.
[0048] The non-aqueous solvent may be a carbonate compound, a carboxylate compound, an ether compound, another organic solvent, or a combination thereof.
[0049] The above carbonate compound may be a chain-type carbonate compound, a cyclic carbonate compound, a fluorocarbonate compound, or a combination thereof.
[0050] Examples of the chain-type carbonate compounds mentioned above include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methylpropyl carbonate (MPC), ethylpropyl carbonate (EPC), methyl ethyl carbonate (MEC), and combinations thereof. Examples of cyclic carbonate compounds include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylethylene carbonate (VEC), and combinations thereof. Examples of fluorocarbonate compounds include fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate, and combinations thereof.
[0051] Examples of the carboxylate compounds mentioned above include methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone, mevalonolactone, caprolactone, and combinations thereof.
[0052] Examples of the above ether compounds include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, and combinations thereof.
[0053] Examples of the above other organic solvents include dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, phosphate esters, and combinations thereof.
[0054] The manufacturing process of the electrochemical device (1) is well known to those skilled in the art, and the present application is not limited in any particular way. For example, the electrochemical device can be manufactured through the following process. That is, it can be manufactured by overlapping the positive and negative electrodes through a separator, and, if necessary, by winding, folding, etc., placing them in a case, injecting an electrolyte into the case, and sealing it. The separator used is the separator provided in the present application. Additionally, if necessary, an overcurrent protection element, a conductive plate, etc., may be placed in the case to prevent pressure rise and overcharging / discharging inside the electrochemical device.
[0055] Referring to FIG. 4, a schematic three-dimensional view of an electronic device (100) provided in an embodiment of the present application is shown. The present application further provides an electronic device (100), said electronic device (100) includes an electrochemical device (1). FIG. 4 illustrates the case where the electronic device (100) is a mobile phone, and in other embodiments, the electronic device (100) of the present application is not particularly limited and may be any electronic device known in the prior art. In some embodiments, the electronic device (100) may include, but is not limited to, a notebook, a pen input computer, a mobile computer, an e-book player, a portable telephone, a portable fax machine, a portable copier, a portable printer, a headset, a video player, a liquid crystal TV, a portable vacuum cleaner, a portable CD player, a minidisc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, an assist bicycle, a bicycle, lighting equipment, a toy, a game console, a watch, a power tool, a flashlight, a camera, a household high-capacity storage battery, and a lithium-ion capacitor.
[0056] Polar edge thickness COV test:
[0057] 1) Separate the electrode from the completed battery in an environment of (25±3)℃. Wipe off any electrolyte remaining on the surface of the electrode with a dust-free paper.
[0058] 2) Cut the electrode to obtain an electrode sample of a certain area.
[0059] 3) Measure the thickness of the edge of the electrode near the tab of the electrode sample in 2) using a micrometer, test the thickness values at 15 different points along the edge of the electrode in sequence, and calculate the COV value of the thickness values at all test points.
[0060] Battery Volumetric Energy Density Test:
[0061] 1) After charging the battery to 3.6V with a constant current in an environment of (25±3)℃, discharge it to 2.5V at a 0.5C multiplier to obtain the actual capacity Cap.
[0062] 2) The battery discharge platform is E.
[0063] 3) Measure the length, width, and height of the battery, and take the average value by measuring 10 points on each side, and the volume V = length * width * height.
[0064] 4) Volumetric energy density V.ED = Cap*E / V.
[0065] Example 1
[0066] <1-1. Preparation of Anode Sections>
[0067] Lithium cobaltate, acetylene black, and polyvinylidene fluoride (PVDF), which are cathode active materials, are mixed in a mass ratio of 94:3:3, and then N-methylpyrrolidone (NMP) is added as a solvent to prepare a slurry with a solid content of 75%, which is then uniformly stirred. The slurry is evenly applied to one surface of an aluminum foil with a thickness of 12 μm, dried at 90°C, and then cold-pressed to obtain a cathode electrode with a cathode active material layer thickness of 100 μm. The above steps are then repeated on the other surface of the cathode electrode to obtain a cathode electrode coated with a cathode active material layer on both sides. Here, the thickness L of the cathode active material layer (first active material layer) is 100 μm, and the coating weight of the first active material layer is 0.2 mg / mm². 2 The compression density of the first active material layer is 2.0 g / cc.
[0068] An insulating layer is installed at the edge of the positive active material layer on one side near the tab of the positive electrode, wherein the insulating layer composition (mass ratio) is PVDF:boehmite = 40%:60%, the thickness H of the second region of the insulating layer is 20 μm, the width W of the insulating layer is 1.2 mm, and cotα corresponding to the acute angle α is 1.
[0069] Cut the positive electrode piece to a size of 74mm × 867mm, weld the tab, and then use it.
[0070] <1-2. Preparation of Cathode Pieces>
[0071] Synthetic graphite, acetylene black, styrene-butadiene rubber, and sodium carboxymethylcellulose, which are cathode active materials, are mixed in a mass ratio of 96:1:1.5:1.5, and deionized water is added as a solvent to prepare a slurry with a solid content of 70%, which is then uniformly stirred. The slurry is evenly applied to one surface of a copper foil with a thickness of 8 μm, dried at 110°C, and then cold-pressed to obtain a cathode electrode plate with a cathode active material layer coated on one side with a thickness of 150 μm. The above coating step is then repeated on the other surface of the cathode electrode plate to obtain a cathode electrode plate with cathode active material layers coated on both sides. The cathode electrode plate is cut to a size of 74 mm × 867 mm, tapped, and then used.
[0072] <1-3. Preparation of Electrolyte>
[0073] In an environment with a moisture content of less than 10 ppm, non-aqueous organic solvents such as ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), propylpropionate (PP), and vinylene carbonate (VC) are mixed in a mass ratio of 20:30:20:28:2, and then lithium hexafluorophosphate (LiPF6) is added to the non-aqueous organic solvent to dissolve and mix, thereby obtaining an electrolyte, wherein the mass ratio of LiPF6 to the non-aqueous organic solvent is 8:92.
[0074] <1-4 Manufacture of Lithium-ion Batteries>
[0075] The positive electrode and the negative electrode are wound, and the positive electrode and the negative electrode are separated using a polyethylene (PE) film as a separator, and an electrode assembly is manufactured. The electrode assembly is placed in an aluminum plastic film packaging bag, moisture is removed at 80°C, a prepared electrolyte is injected, and a lithium-ion battery is obtained through processes such as vacuum packaging, settling, forming, and molding.
[0076] Example 2
[0077] Example 2 has the same lithium-ion battery manufacturing process as Example 1 but differs in component parameters, wherein the thickness L of the positive active material (first active material layer) is 100 μm and the coating weight of the first active material layer is 0.2 mg / mm 2 The compression density of the first active material layer is 2.0 g / cc, the insulating layer composition (mass ratio) is PVDF:boehmite = 40%:60%, the thickness H of the second insulating layer region is 40 μm, the width W of the insulating layer is 1.2 mm, and cotα corresponding to the acute angle α is 1.
[0078] Example 3
[0079] Example 3 has the same lithium-ion battery manufacturing process as Example 1 but differs in component parameters, wherein the thickness L of the positive active material (first active material layer) is 100 μm and the coating weight of the first active material layer is 0.2 mg / mm 2 The compression density of the first active material layer is 2.0 g / cc, the insulating layer composition (mass ratio) is PVDF:boehmite = 40%:60%, the thickness H of the second insulating layer region is 50 μm, the width W of the insulating layer is 1.2 mm, and cotα corresponding to the acute angle α is 1.
[0080] Example 4
[0081] Example 4 has the same lithium-ion battery manufacturing process as Example 1 but differs in component parameters, wherein the thickness L of the positive active material (first active material layer) is 100 μm and the coating weight of the first active material layer is 0.2 mg / mm 2 The compression density of the first active material layer is 2.0 g / cc, the insulating layer composition (mass ratio) is PVDF:boehmite = 40%:60%, the thickness H of the second insulating layer region is 80 μm, the width W of the insulating layer is 1.2 mm, and cotα corresponding to the acute angle α is 1.
[0082] Example 5
[0083] Example 5 has the same lithium-ion battery manufacturing process as Example 1 but differs in component parameters, wherein the thickness L of the positive active material (first active material layer) is 125 μm and the coating weight of the first active material layer is 0.2 mg / mm 2 The compression density of the first active material layer is 2.0 g / cc, the insulating layer composition (mass ratio) is PVDF:boehmite = 40%:60%, the thickness H of the second insulating layer region is 100 μm, the width W of the insulating layer is 1.2 mm, and cotα corresponding to the acute angle α is 1.
[0084] Example 6
[0085] Example 6 has the same lithium-ion battery manufacturing process as Example 1 but differs in component parameters, wherein the thickness L of the positive active material (first active material layer) is 100 μm and the coating weight of the first active material layer is 0.2 mg / mm 2 The compression density of the first active material layer is 2.0 g / cc, the insulating layer composition (mass ratio) is PVDF:boehmite = 40%:60%, the thickness H of the second insulating layer region is 50 μm, the width W of the insulating layer is 1 mm, and cotα corresponding to the acute angle α is 1.
[0086] Example 7
[0087] Example 7 has the same lithium-ion battery manufacturing process as Example 1 but differs in component parameters, wherein the thickness L of the positive active material (first active material layer) is 100 μm and the coating weight of the first active material layer is 0.2 mg / mm 2 The compression density of the first active material layer is 2.0 g / cc, the insulating layer composition (mass ratio) is PVDF:boehmite = 40%:60%, the thickness H of the second insulating layer region is 50 μm, the width W of the insulating layer is 1.2 mm, and cotα corresponding to the acute angle α is 1.
[0088] Example 8
[0089] Example 8 has the same lithium-ion battery manufacturing process as Example 1 but differs in component parameters, wherein the thickness L of the positive active material (first active material layer) is 100 μm and the coating weight of the first active material layer is 0.2 mg / mm 2 , the compression density of the first active material layer is 2.0 g / cc, the insulating layer composition (mass ratio) is PVDF: boehmite = 40%:60%, the thickness H of the second insulating layer region is 80 μm, the width W of the insulating layer is 10 mm, and cotα corresponding to the acute angle α is 1.
[0090] Example 9
[0091] Example 9 has the same lithium-ion battery manufacturing process as Example 1 but differs in component parameters, wherein the thickness L of the positive active material (first active material layer) is 100 μm and the coating weight of the first active material layer is 0.2 mg / mm 2 The compression density of the first active material layer is 2.0 g / cc, the insulating layer composition (mass ratio) is PVDF:boehmite = 40%:60%, the thickness H of the second insulating layer region is 30 μm, the width W of the insulating layer is 1.2 mm, and cotα corresponding to the acute angle α is 1.
[0092] Example 10
[0093] Example 10 has the same lithium-ion battery manufacturing process as Example 1 but differs in component parameters, wherein the thickness L of the positive active material (first active material layer) is 100 μm and the coating weight of the first active material layer is 0.2 mg / mm 2 The compression density of the first active material layer is 2.0 g / cc, the insulating layer composition (mass ratio) is PVDF:boehmite = 40%:60%, the thickness H of the second insulating layer region is 50 μm, the width W of the insulating layer is 10 mm, and cotα corresponding to the acute angle α is 0.3.
[0094] Example 11
[0095] Example 11 has the same lithium-ion battery manufacturing process as Example 1 but differs in component parameters, wherein the thickness L of the positive active material (first active material layer) is 100 μm and the coating weight of the first active material layer is 0.2 mg / mm 2 , the compression density of the first active material layer is 2.0 g / cc, the insulating layer composition (mass ratio) is PVDF: boehmite = 40%:60%, the thickness H of the second insulating layer region is 80 μm, the width W of the insulating layer is 10 mm, and cotα corresponding to the acute angle α is 1.
[0096] Example 12
[0097] Example 12 has the same lithium-ion battery manufacturing process as Example 1 but differs in component parameters, wherein the thickness L of the positive active material (first active material layer) is 30 μm and the coating weight of the first active material layer is 0.06 mg / mm 2 The compression density of the first active material layer is 2.0 g / cc, the insulating layer composition (mass ratio) is PVDF:boehmite = 40%:60%, the thickness H of the second insulating layer region is 24 μm, the width W of the insulating layer is 1.2 mm, and cotα corresponding to the acute angle α is 1.
[0098] Example 13
[0099] Example 13 has the same lithium-ion battery manufacturing process as Example 1 but differs in component parameters, wherein the thickness L of the positive active material (first active material layer) is 175 μm and the coating weight of the first active material layer is 0.35 mg / mm 2 The compression density of the first active material layer is 2.0 g / cc, the insulating layer composition (mass ratio) is PVDF:boehmite = 40%:60%, the thickness H of the second insulating layer region is 88 μm, the width W of the insulating layer is 1.2 mm, and cotα corresponding to the acute angle α is 1.
[0100] Example 14
[0101] Example 14 has the same lithium-ion battery manufacturing process as Example 1 but differs in component parameters, wherein the thickness L of the positive active material (first active material layer) is 88 μm and the coating weight of the first active material layer is 0.35 mg / mm 2 The compression density of the first active material layer is 4.0 g / cc, the insulating layer composition (mass ratio) is PVDF:boehmite = 40%:60%, the thickness H of the second insulating layer region is 44 μm, the width W of the insulating layer is 1.2 mm, and cotα corresponding to the acute angle α is 1.
[0102] Example 15
[0103] Example 15 has the same lithium-ion battery manufacturing process as Example 1 but differs in component parameters, wherein the thickness L of the positive active material (first active material layer) is 58 μm and the coating weight of the first active material layer is 0.35 mg / mm 2 The compression density of the first active material layer is 6.0 g / cc, the insulating layer composition (mass ratio) is PVDF:boehmite = 40%:60%, the thickness H of the second insulating layer region is 30 μm, the width W of the insulating layer is 1.2 mm, and cotα corresponding to the acute angle α is 1.
[0104] Example 16
[0105] Example 16 has the same lithium-ion battery manufacturing process as Example 1 but differs in component parameters, wherein the thickness L of the positive active material (first active material layer) is 100 μm and the coating weight of the first active material layer is 0.2 mg / mm 2 The compression density of the first active material layer is 2.0 g / cc, the insulating layer composition (mass ratio) is polyacrylic acid:zirconium oxide = 30%:70%, the thickness H of the second insulating layer region is 50 μm, the width W of the insulating layer is 1.2 mm, and cotα corresponding to the acute angle α is 1.
[0106] Example 17
[0107] Example 17 has the same lithium-ion battery manufacturing process as Example 1 but differs in component parameters, wherein the thickness L of the positive active material (first active material layer) is 100 μm and the coating weight of the first active material layer is 0.2 mg / mm 2 The compression density of the first active material layer is 2.0 g / cc, the insulating layer composition (mass ratio) is PVDF:boehmite = 40%:60%, the thickness H of the second insulating layer region is 87.5 μm, the width W of the insulating layer is 1 mm, and cotα corresponding to the acute angle α is 11.4.
[0108] Comparative Example 1
[0109] Comparative Example 1 has the same lithium-ion battery manufacturing process as Example 1 but differs in component parameters, wherein the thickness L of the positive active material (first active material layer) is 30 μm and the coating weight of the first active material layer is 0.045 mg / mm 2 The compression density of the first active material layer is 1.5 g / cc, the insulating layer composition (mass ratio) is PVDF:boehmite = 40%:60%, the thickness H of the second insulating layer region is 30 μm, and the width W of the insulating layer is 1 mm, so the insulating layer is not thin.
[0110] Comparative Example 2
[0111] Comparative Example 2 has the same lithium-ion battery manufacturing process as Example 1 but differs in component parameters, wherein the thickness L of the positive active material (first active material layer) is 100 μm and the coating weight of the first active material layer is 0.2 mg / mm 2 The compression density of the first active material layer is 2.0 g / cc, the insulating layer composition (mass ratio) is PVDF:boehmite = 40%:60%, the thickness H of the second insulating layer region is 50 μm, and the width W of the insulating layer is 1.2 mm, so the insulating layer is not thin.
[0112] Comparative Example 3
[0113] Comparative Example 3 has the same lithium-ion battery manufacturing process as Example 1 but differs in component parameters, wherein the thickness L of the positive active material (first active material layer) is 100 μm and the coating weight of the first active material layer is 0.2 mg / mm 2 The compression density of the first active material layer is 2.0 g / cc, the insulating layer composition (mass ratio) is PVDF:boehmite = 40%:60%, the thickness H of the second insulating layer region is 0 μm, and the width W of the insulating layer is 1.2 mm, so the insulating layer is not thin.
[0114] For the above Examples 1 to 17 and Comparative Examples 1 to 3, processes such as winding and cold pressing were performed, and the appearance of the electrodes was observed to calculate the energy density. The results are as shown in Table 1 below.
[0115] Table 1 Examples Thickness H / μm of the second region of the insulating layer Insulation layer width W / mm W / H cotα Thickness of the first active material layer L / μm H / L Coating weight of the active substance layer (mg / mm²) 2 ) Compressed density of the active material layer (g / cc) Insulating layer components (mass ratio) Extreme appearance Volumetric energy density V.ED / Wh / L 1 20 1.2 60 1 100 0.2 0.2 2.0 PVDF:Boehmite = 40%:60% The edge of the polarity is not bulging, and the thickness of the polarity edge is COV≤0.5% 303.7 2 40 1.2 30 1 100 0.4 0.2 2.0 PVDF:Boehmite = 40%:60% The edge of the polarity is not bulging, and the thickness of the polarity edge is COV≤0.5% 308.4 3 50 1.2 24 1 100 0.5 0.2 2.0 PVDF:Boehmite = 40%:60% The edge of the polarity is not bulging, and the thickness of the polarity edge is COV≤0.5% 305.9 4 80 1.2 15 1 100 0.8 0.2 2.0 PVDF:Boehmite = 40%:60% The edge of the polarity is not bulging, and the thickness of the polarity edge is COV≤0.5% 304.1 5 100 1.2 12 1 125 0.8 0.25 2.0 PVDF:Boehmite = 40%:60% The edge of the polarity is not bulging, and the thickness of the polarity edge is COV≤0.5% 308.1 6 50 1 20 1 100 0.5 0.2 2.0 PVDF:Boehmite = 40%:60% The edge of the polarity is not bulging, and the thickness of the polarity edge is COV≤0.5% 306.4 7 50 1.2 24 1 100 0.5 0.2 2.0 PVDF:Boehmite = 40%:60% The edge of the polarity is not bulging, and the thickness of the polarity edge is COV≤0.5% 303.4 8 80 10 125 1 100 0.8 0.2 2.0 PVDF:Boehmite = 40%:60% The edge of the polarity is not bulging, and the thickness of the polarity edge is COV≤0.5% 309.0 9 30 1.2 40 1 100 0.3 0.2 2.0 PVDF:Boehmite = 40%:60% The edge of the polarity is not bulging, and the thickness of the polarity edge is COV≤0.5% 301.4 10 50 10 50 0.3 100 0.5 0.2 2.0 PVDF:Boehmite = 40%:60% The edge of the polarity is not bulging, and the thickness of the polarity edge is COV≤0.5% 307.6 11 80 10 50 1 100 0.5 0.2 2.0 PVDF:Boehmite = 40%:60% The edge of the polarity is not bulging, and the thickness of the polarity edge is COV≤0.5% 300.2 12 24 1.2 50 1 30 0.8 0.06 2.0 PVDF:Boehmite = 40%:60% The edge of the polarity is not bulging, and the thickness of the polarity edge is COV≤0.5% 201.4 13 88 1.2 14 11.4 175 0.5 0.35 2.0 PVDF:Boehmite = 40%:60% The edge of the polarity is not bulging, and the thickness of the polarity edge is COV≤0.5% 448.2 14 44 1.2 27 1 88 0.5 0.35 4.0 PVDF:Boehmite = 40%:60% The edge of the polarity is not bulging, and the thickness of the polarity edge is COV≤0.5% 375.2 15 30 1.2 40 1 58 0.5 0.35 6.0 PVDF:Boehmite = 40%:60% The edge of the polarity is not bulging, and the thickness of the polarity edge is COV≤0.5% 408.4 16 50 1.2 24 1 100 0.5 0.2 2.0 Polyacrylic acid: Zirconium oxide = 30%:70% The edge of the polarity is not bulging, and the thickness of the polarity edge is COV≤0.5% 302.6 17 87.5 1 11 11.4 100 0.9 0.2 2.0 PVDF:Boehmite = 40%:60% The edge of the polarity is not bulging, and the thickness of the polarity edge is COV≤0.5% 253.1 Comparative Example 1 30 1 33 / 30 1.0 0.045 1.5 PVDF:Boehmite = 40%:60% The edge of the polarity does not bulge, and the thickness of the polarity edge is COV=0.7% 180.5 Comparative Example 2 50 1.2 24 / 100 0.5 0.2 2.0 PVDF:Boehmite = 40%:60% The edge of the polarity is swollen, and the thickness of the polarity edge is COV≤0.5% / Comparative Example 3 0 1.2 / / 100 0.0 0.2 2.0 PVDF:Boehmite = 40%:60% The edge of the polarity is swollen, and the thickness of the polarity edge is COV > 1% /
[0116] The electrochemical device of the present application, compared to the prior art, prevents short circuits in the electrochemical device by installing a first active material layer and an insulating layer adjacent to the electrode piece so that the insulating layer covers a portion of the cutting burr of the first current collector and the tap, and by installing a thin first region on the outer side of the insulating layer to control the ratio between the thickness of the insulating layer and the thickness of the first active material layer and the thin shape of the insulating layer, thereby improving the uniformity of the force received during the rolling process of the electrode piece while ensuring the safety of the electrochemical device, and thus improving the overall performance of the electrochemical device. The specific embodiments of the present application have been described above with reference to the attached drawings. However, those skilled in the art will understand that various modifications and substitutions may be made to specific embodiments of the present application without departing from the spirit and scope of the present application. Such modifications and substitutions are within the scope defined in the present application. Explanation of the symbols
[0117] 1: Electrochemical device 10: Play 11: The entire first congregation 12: 1st tab 13: First active substance layer 14: Insulating layer 141: First Zone 142: Second Zone 143: First surface α: acute angle 100: Electronic device
Claims
Claim 1 An electrochemical device comprising an electrode, wherein the electrode comprises a first current collector, a first tab protruding from the first current collector, a first active material layer installed on at least one surface of the first current collector, and an insulating layer installed along a side of the first current collector near the first tab and adjacent to the first active material layer, wherein the insulating layer comprises a first region and a second region, wherein the first region is installed on one side near the first tab, and the second region is installed far from the first tab and adjacent to the first active material layer, and the thickness of the insulating layer in the first region is smaller than the thickness of the insulating layer in the second region, wherein the first region comprises a first surface, and the plane on which the first surface is located intersects the plane on which the first current collector is located to form an acute angle α, and the range of the acute angle α is 5° to 75°, and the thickness of the second region is H, and the thickness H of the second region and the thickness L of the first active material layer An electrochemical device characterized by satisfying the relationship 0.3≤H / L≤0.
8. Claim 2 An electrochemical apparatus according to claim 1, characterized in that the width of the insulating layer is W, where W / H ≥ cotα. Claim 3 delete Claim 4 An electrochemical device according to claim 2, characterized in that the thickness H of the second region ranges from 20 μm to 100 μm, and the width W of the insulating layer ranges from 1 mm to 10 mm. Claim 5 An electrochemical device according to claim 1, characterized in that the thickness L of the first active material layer ranges from 30 μm to 200 μm. Claim 6 delete Claim 7 In claim 1, the coating weight of the first active substance layer is 0.06 mg / mm 2 Up to 0.35 mg / mm 2 Electrochemical device characterized by being. Claim 8 An electrochemical device according to claim 1, characterized in that the compression density of the first active material layer is 2 g / cc to 6 g / cc. Claim 9 An electrochemical device according to claim 1, wherein the insulating layer comprises inorganic particles and an adhesive, the inorganic particles comprise at least one of boehmite, aluminum oxide, zirconium oxide, boron oxide, or hexagonal boron nitride, and the adhesive comprises at least one of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, or sodium carboxymethylcellulose. Claim 10 An electronic device characterized by including an electrochemical device according to any one of claims 1, 2, 4, 5, 7 through 9.
Citation Information
Patent Citations
Power storage element
JP2017188371A
Nonaqueous electrolyte secondary cell and method formanufacturing electrode used for the same
KR1020040076831A
